Is there really a black hole at the center of NGC 4041? Constraints from gas kinematics - Marconi, A; Axon, D; Capetti, A; Maciejewski, W; Atkinson, J; Batcheldor, D; Binney, J; Carollo, M; Dressel, L; Ford, H; Gerssen, J; Hughes, M; et al. (Institute of Physics Publishing, 2003)
We present Space Telescope Imaging Spectrograph spectra of the Sbc spiral galaxy NGC 4041, which were used to map the velocity field of the gas in its nuclear region. We detect the presence of a compact (r ≃ 0″.4 ≃ 40 pc), high surface brightness, rotating nuclear disk cospatial with a nuclear star cluster. The disk is characterized by a rotation curve with a peak-to-peak amplitude of ∼40 km s-1 and is systematically blueshifted by ∼10-20 km s-1 with respect to the galaxy systemic velocity. With the standard assumption of constant mass-to-light ratio and with the nuclear disk inclination taken from the outer disk, we find that a dark point mass of (1-0.7+0.6) × 107 M⊙ is needed to reproduce the observed rotation curve. However, the observed blueshift suggests the possibility that the nuclear disk could be dynamically decoupled. Following this line of reasoning, we relax the standard assumptions and find that the kinematical data can be accounted for by the stellar mass provided that either the central mass-to-light ratio is increased by a factor of ∼2 or the inclination is allowed to vary. This model results in a 3 σ upper limit of 6 × 106 M⊙ on the mass of any nuclear black hole (BH). Overall, our analysis only allows us to set an upper limit of 2 × 107 M⊙ on the mass of the nuclear BH. If this upper limit is taken in conjunction with an estimated bulge B magnitude of -17.7 and with a central stellar velocity dispersion of ≃95 km s-1, then these results are not inconsistent with both the MBH-Lsph and the MBH-σ* correlations. Constraints on BH masses in spiral galaxies of types as late as Sbc are still very scarce; therefore, the present result adds an important new data point to our understanding of BH demography.